Trade and Uncertainty - Dennis Novy; Alan Taylor (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2014)
We offer a new explanation as to why international trade is so volatile in response to economic shocks. Our approach combines the uncertainty shock idea of Bloom (2009) with a model of trade, extending the idea to the open economy. Firms import intermediate inputs from home or foreign suppliers, but with higher costs in the latter case. Due to fixed costs of ordering firms hold an inventory of intermediates. In response to an uncertainty shock firms optimally adjust their inventory by cutting orders of foreign intermediates disproportionately strongly. In the aggregate, this leads to a bigger contraction in international trade flows than in domestic activity. We confront the model with newly-compiled U.S. import data and industrial production data going back to 1962, and also with disaggregated data back to 1989. Our results suggest a tight link between uncertainty and fluctuations in international trade.
Keywords: F10; E30; F40; 330